2016
DOI: 10.1016/j.ijscr.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor presenting as ileocecal intussusception—A case report

Abstract: HighlightsInflammatory myofibroblastic tumor (IMFT) is an uncommon mesenchymal solid tumor that usually affects children and young adults.We present a case of gastrointestinal involvement by IMFT that presented as an ileocecal intussusception in an adult.The treatment is surgical and prognosis is good if total surgical excision is accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Distant metastasis is rare, often related to the lack of anaplastic lymphoma kinase (ALK) reactivity. Serial radiological and ESR measurements may help to assess early recurrence [ 14 , 15 ]. In this case report the patient was followed with clinical examination, ESR, and abdominal ultrasound; there was no sign of recurrence during the first year of follow-up.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Distant metastasis is rare, often related to the lack of anaplastic lymphoma kinase (ALK) reactivity. Serial radiological and ESR measurements may help to assess early recurrence [ 14 , 15 ]. In this case report the patient was followed with clinical examination, ESR, and abdominal ultrasound; there was no sign of recurrence during the first year of follow-up.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Distant metastasis is infrequent and is often connected to the absence of anaplastic lymphoma kinase (ALK) reactivity. Employing serial radiological assessments and measurements of erythrocyte sedimentation rate (ESR) can aid in detecting early recurrence [ 8 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the tumor was an intraluminal mass with a focal depression secured by normal mucosa similar to a classic GI stromal tumor (GIST) or lymphoma. It has been reported that the diagnosis of IMT from other malignant, infectious, and congenital lesions depends on the histologic examination of the tissue [ 13 ]. Spindle cells along with a variable infiltration of dense polymorphic mononuclear inflammatory cells made out of lymphocytes, plasma cells, histiocytes, and occasional eosinophils are histological characteristics of IMTs, which arrange in short fascicles with focal storiform architecture, as a result of the spindle cells [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%